Yield and Oil Content of Mint under Different Nitrogen Fertilizer Treatments - Hamed KESHAVARZ; Seyed Ali Mohammad MODARRES SANAVY (Notulae Scientia Biologicae, 2018)
Two species of mint Mentha piperitha (peppermint) and M. arvensis (Japanese mint) are widely cultivated in Iran, but their response to fertilizer regime has not been evaluated so far. A field experiment was conducted to investigate the effects of different organic and chemical fertilizer treatments [Control, 100% urea (95 kg N ha−1), 75% urea (71.25 kg N ha-1) + 25% vermicompost (3.3 t ha-1), 50% urea (47.5 kg N ha-1) + 50% vermicompost (6.75 t ha-1), 25% urea (23.75 kg N ha-1) + 75% vermicompost (10.1 t ha-1) and 100% vermicompost (13.5 ton ha-1)] on essential oil contents, yield and yield components of the two species of mint. Peppermint provided grater plant height, number of internodes, number of leaf and oil percentage compared with the Japanese mint under study. The results indicated that, irrespective of the mint species, plants treated with combined chemical and organic fertilizer presented taller plants, higher oil contents and oil yield compared with solo chemical or organic fertilizers. Oil percentage and essential oil yield of mint increased significantly under the treatment with 25% urea (23.75 kg N ha−1) + 75% vermicompost (10.1 t ha-1). Plant height and number of leaf increased along the replacement of organic fertilizer with chemical fertilizers. The results showed that there was a positive and significant correlation with leaf number and essential oil yield. Application of vermicompost in combination with chemical fertilizer increased plant height, oil percentage and essential oil in both species, suggesting that organic and chemical fertilizer combination improves performance and environmental sustainability.